Potential biodegradable Zn-Cu binary alloys developed for cardiovascular implant applications. (August 2017) - Tang, Zibo; Niu, Jialin; Huang, Hua; Zhang, Hua; Pei, Jia; Ou, Jingmin; Yuan, Guangyin
Abstract: Binary Zn-Cu alloy system is developed as potential biodegradable materials for cardiovascular implant application. The microstructure, tensile properties, in vitro corrosion behavior, cytotoxicity and antibacterial property of as-extruded Zn-xCu (x=1, 2, 3, and 4 wt%) alloys are investigated systematically. It shows that as Cu content increases more CuZn5 phase precipitates. After extrusion, the CuZn5 phases are broken and the grains of Zn-xCu alloys are refined. Tensile test shows that Cu addition could significantly improve the mechanical properties of Zn-xCu alloys. Particularly, the elongation of the Zn-4Cu reaches 50.6±2.8%, which could facilitate the micro-tubes processing for stent fabrication. The micro-tubes of 3 mm in outer diameter and 0.2 mm in thickness as well as vascular stents have been fabricated successfully using the Zn-Cu binary alloy. The degradation rates of Zn-xCu alloys in c-SBF solution are quite low, which vary from 22.1±4.7 to 33.0±1.0 μm year −1 . With increasing Cu concentration, the corrosion rates of the Zn-xCu alloys generally exhibit a little increase compared with pure Zn, which show no significant difference among Zn-xCu alloys. In vitro test shows that Zn-xCu alloys exhibit acceptable cytotoxicity to human endothelial cells and the antibacterial property (S. aureus) is perfect when Cu concentration is higher than 2 wt%. Therefore, the newly developed Zn-xCu binary alloys could be promising candidates for biodegradable cardiovascular implant application due to their excellent combination of strength and ductility, low degradation rates, acceptable cytotoxicity and good antibacterial property. Graphical abstract: Highlights: Zn-xCu alloys are newly developed as biodegradable materials. Mechanical properties of Zn-xCu alloys are enhanced with Cu addition. Zn-xCu alloys possess moderate corrosion rates and acceptable biocompatibility. Zn-xCu alloys possess good antibacterial property. Zn-xCu alloys are promising candidate for cardiovascular stent applications.